Endoscopic sensing of distal lung physiology. (January 2019) - Choudhury, Debaditya; Tanner, Michael G; McAughtrie, Sarah; Yu, Fei; Mills, Bethany; Choudhary, Tushar R; Seth, Sohan; Craven, Thomas H; Stone, James M; Mati, Ioulia K; Campbell, Colin J; Bradley, Mark; et al.
Abstract: The alveolar space forms the distal end of the respiratory tract where chemoreceptor driven gas exchange processes occur. In healthy humans, the physiological state within the alveoli is tightly regulated by normal homeostatic mechanisms. However, pulmonary abnormalities such as chronic obstructive pulmonary disease may induce significant perturbation of the homeostatic baselines of physiology as well as cause host tissue damage. Therefore, physiological parameters (pH, glucose, oxygen tension) within the alveolar space provide a key biomarker of innate defence. Here, we discuss an endoscope-deployable fibre-optic optrode for sensing pH in the alveolar space. In order to circumvent the unwanted Raman signal generated within the fibre, the optrode consists of a custom asymmetric dual-core optical fibre designed for spatially separated optical pump delivery and SERS signal collection. pH sensing is achieved using the surface enhanced Raman spectroscopy (SERS) signal generated from functionalised gold nanoshell sensors. We show a ∼ 100-fold increase in SERS signal-to-fibre background ratio and demonstrate multiple site pH sensing in the alveoli of an ex vivo ovine lung model with a measurement accuracy of ± 0.07 pH unit.